BENDEL KESLINGMAS NO 122TAHUN 2014 - Hani, Desita Frida, Nirma Dedi, Dkk (Poltekkes Kemenkes Semarang, 2014)
RSUD Prof. Dr. Margono Soekarjo Purwokerto is the regional hospital type B area that provide specialized medical care and subspecialty limited. Pavilion Soeparjo Rustam treatment room is a treatment that treating all kinds of diseases both infectious diseases and non-infectious diseases, so the potential occurrence of nosocomial infection. The purpose of this study was to determine of disinfection effectiveness in reducing the number of germs air in Paviliun Soeparjo Rustam treatment room RSUD Prof. Dr. Margono Soekarjo Purwokerto. This research is analytic research with cross sectional approach. Type of variable used is the free variable (disinfection), dependent variable (number of air germs), potentially confounding variables (temperature, humidity, lighting, ventilation and a vast volume of space). According to the result of investigation, the average number of germs air before disinfection is 265 CFU/m3, after disinfection is 20 CFU/m3. Average effective disinfection is 92.45%. The average temperature was 23.5 oC. The average humidity was 50.55 %. The average lighting is 179.7 Lux. Extensive ventilation in Paviliun Soeparjo Rustam treatment room is 0.9 m2. Room volume is 36 m3. Researchers concluded the use of disinfection is effective in reducing the number of air germs. The researcher gives suggestion if another researcher wants to do a disinfectant they must using full PPE.